Environmental conditions influence allometric patterns in the blow fly, Chrysomya albiceps - Battan Horenstein, Moira (2011)
The objective of this research was to study variations in allometry of body characters in females and males of two populations of blow flies, Chrysomya albiceps (Wiedemann) (Diptera: Calliphoridae), under different environmental conditions to establish patterns of morphologicalvvariation. Body size of both males and females in the experimental population was significantly higher than in the individuals of the natural population, indicating an important influence of food on body size. All genitalic and non-genitalic characters in males and females of the two populations showed a trend towards negative allometry rather than isometry. Allometric patterns were modified in both sexes and between populations. The data show generally larger allometric slopes in females than in males. We confirmed that the environmental conditions have an important effect on allometric patterns and body size.